ANALISIS ASOSIASI DAUN SANG (Johannesteijsmannia altifrons) DENGAN JENIS-JENIS PALEM DI RESORT SEI BETUNG, TAMAN NASIONAL GUNUNG LEUSER, KABUPATEN LANGKAT, SUMATERA UTARA - Amos Ferdinan Sihombing; Nelly Anna; Kansih Sri Hartini (Program studi Kehutanan USU, 2015)
Daun Sang is an endemic species that can be found in Gunung Leuser National Park and Bukit Tiga Puluh National Park. This palm is thought to have associations with other palm. Where around Daun Sang grow there are palm types Lipai (Licuala spinosa), but not always around Lipai grow Daun Sang are. Daun Sang need shade to grow because these palm is sensitive to the sunlight. This study aimed to analyze the association of daun sang by some kind of palm that grows around in order to conservation and optimize the cultivation of the daun sang. The method used is a descriptive method with observation of the Daun Sang number and some kind of of palms around it done intentionally (purposive sampling). The method is performed by making 2 plot observations, each size is 100m × 100m, then divided by making the sample plots of 20m × 20m. Observed data were processed using 2 x 2 contingency table, and then calculated by the chi-square test formulations and Jaccard index to calculate the extent of the association. three species of palm found in the study site there are pinanga speciosa, tetradactylus and Plectomiopsis Calamus sp. The results showed that daun sang are not associated with Pinanga speciosa. Association occurs between daun sang with the Calamus tetradactylus and daun sang with Plectomiopsis sp. The highest level of association occurs in Daun Sang and Calamus tetradactylus with maximum association index value of 1. The level of association between Daun Sang with Plectomiopsis sp. approaching the maximum value of the association index in 0.84.Key word : Daun Sang (Johannesteijsmania altifrons), Association Analysis, Ressort Sei Betung